Effect of Extinction on Separation of Nanoparticle Enantiomers With Chiral Optical Forces - Semen A. Andronaki; Weiren Zhu; Mikhail Yu. Leonov; Alexey G. Shalkovskiy; Alexander V. Baranov; Anatoly V. Fedorov; Ivan D. Rukhlenko (IEEE Photonics Journal, 2017)
Separation of enantiomers of chiral inorganic nanoparticles can be performed using enantioselective optical forces that are strong enough to make the ordered drift of nanoparticles faster than their movement down a concentration gradient. Here, we solve the problem of nanoparticle diffusion in a bounded domain in the presence of an exponentially decaying driving force, which can represent a chiral force exerted on nanoparticle enantiomers by a circularly polarized light beam exhibiting either scattering, absorption, or both. We analyze the steady state spatial distributions of two basic purity measures of chiral mixtures, showing that extinction puts a fundamental limit on the degree of enantiopurification achievable with optical forces. Our solution can be used to model resolution of racemates of any kind of chiral inorganic nanoparticles that strongly interact with light.